2014
DOI: 10.1002/bab.1143
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo cytokine production in peripheral blood mononuclear cells after their stimulation with dsRNA of natural origin

Abstract: Double-stranded RNA (dsRNA) is a pathogen-associated molecular pattern, known for its ability to induce antiviral response and enhance communication between cells mediating innate and adaptive immune responses. The aim of this study was to characterize the effect of the dsRNA-containing product Larifan on the production of a wide spectrum of cytokines and chemokines in ex vivo cultivated peripheral blood mononuclear cells. Concentrations of 29 different cytokines were detected by a Luminex® 200™ System using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…This particular function is promoted by various factors, such as amorphous silica particles capable to increase IL-1β and IL-8 production [25] , and cortisol that have been shown to suppress secretion of IL-1β, IL-6, IL-17 and G-CSF [26] . Recently, Veinalde et al [27] have reported that double stranded RNA has the capacity to induce PBMC to produce a considerable number of both pro-and antiinflammatory cytokines. Metal particles, such as titanium and stainless steel originating in patients with implanted medical devices have been shown to enhance increased production of IL-6 and IL-1 by PBMC, but to lower the level of TNF-α [28] .…”
Section: Peripheral Blood Mononuclear Cells and Cytokine Productionmentioning
confidence: 99%
“…This particular function is promoted by various factors, such as amorphous silica particles capable to increase IL-1β and IL-8 production [25] , and cortisol that have been shown to suppress secretion of IL-1β, IL-6, IL-17 and G-CSF [26] . Recently, Veinalde et al [27] have reported that double stranded RNA has the capacity to induce PBMC to produce a considerable number of both pro-and antiinflammatory cytokines. Metal particles, such as titanium and stainless steel originating in patients with implanted medical devices have been shown to enhance increased production of IL-6 and IL-1 by PBMC, but to lower the level of TNF-α [28] .…”
Section: Peripheral Blood Mononuclear Cells and Cytokine Productionmentioning
confidence: 99%
“…Larifan also has a potential application in oncology, as it has exhibited an antitumoral effect in several preliminary experimental clinical investigations. The results obtained by this group and described in the paper revealed the pleiotropic effect of Larifan on the immune response.…”
mentioning
confidence: 59%
“…A biotechnological study of Latvian researchers published in this issue is devoted to the characterization of the effect of dsRNA‐containing product Larifan on the production of a wide spectrum of cytokines, which are secreted proteins that possess the ability to modulate immune response, and chemokines whose key function is to traffic various subsets of lymphocytes. Larifan is a pharmaceutical product obtained from Escherichia coli cells infected with a bacteriophage .…”
mentioning
confidence: 99%
“…The preparation has an interferonogenic and immunomodu latory properties. It exhibited an antitumoral effect in the investigations with experimental tumor models [17,18].…”
mentioning
confidence: 98%